Comparative analysis researches positioning strategies leading universities of the country of Western Europe in the international information space - Shcherbak, I. (Problems of Engineer-Pedagogical Education, 2021)
Globalization and informatization of education and the growth of competition in the market of educational services encourages higher education institutions to develop new strategies for their own positioning. The article makes a comparative pedagogical analysis of the strategies for positioning leading universities in the international information space based on scientific works in economics, sociology, management of organizations, and public administration. The scientific research deals with the topical issue of positioning strategies of the leading universities in Western Europe. As a result of the study, it was found that for the successful operation of education institutions, it is necessary to define and apply positioning strategies correctly. The author, based on analysis, synthesis, observation, description and comparison, defines the essence of the concept “strategy of positioning a leading university in the international information space” as an action plan that is a guide to an open dialogue with the world and is aimed at identifying the interests and needs of the target audience; forming a positive image (brand) and maintaining the reputation of a leading institution of higher education in the minds of consumers of educational services or users of educational products (which means the opportunity for applicants and students to study at a leading university, a better chance for graduates to get a well-paid job and for employers to find highly qualified employees, an opportunity for scientists to receive grants and research scholarships, and a chance for heads and teachers to get higher salaries and a position at a prestigious university, etc.) as well as providing convincing information to interested parties about the competitive advantages of education and the prospects they face after graduating from an education institution in the framework of the international space for exchanging and obtaining information through the relationship between the material and objects, subjects and phenomena. Having conducted an analysis and specific research on the development strategy of a university, the author has shown possibilities of solving the topical issues of the development of a production strategy of the enterprise in the course of positioning the leading universities of the countries of Western Europe in the international information space.